2011
DOI: 10.1016/j.econedurev.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Do no-loan policies change the matriculation patterns of low-income students?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…In the past few years, more than 70 institutions, many in the elite private sector, have adopted such programs (Kantrowitz, 2011). Recent analyses by Hillman (2013) and Waddell and Singell (2011) suggest that these programs can influence lower-SES student enrollment. Loan reduction and elimination efforts may well be an effective tool for elite private institutions seeking to bolster lower-SES student enrollment.…”
Section: Pricing Policiesmentioning
confidence: 97%
“…In the past few years, more than 70 institutions, many in the elite private sector, have adopted such programs (Kantrowitz, 2011). Recent analyses by Hillman (2013) and Waddell and Singell (2011) suggest that these programs can influence lower-SES student enrollment. Loan reduction and elimination efforts may well be an effective tool for elite private institutions seeking to bolster lower-SES student enrollment.…”
Section: Pricing Policiesmentioning
confidence: 97%
“…Previous authors have explored the impact of student debt on the uptake of university study with varying results, as recently explicated by Craig and Raisanen (2014). Linsenmeier et al (2006) and Burdman (2005) found that the increased cost of student debt is a barrier to university participation and a heavy long-term burden for students, a finding that contrasts with Tumen and Shulruf (2008) and Waddell and Singell (2011), who concluded that increased debt is not a discouraging factor and is an effective vehicle for access among higher need students. Empirical results vary by region, with previous studies in Europe demonstrating a logical relationship between the level of public support for education and students' socioeconomic background in countries including England, the Netherlands and Spain, but a less clear relationship in Norway, the Czech Republic and Germany (Opheim & Schwarzenberger, 2009).…”
Section: Research Backgroundmentioning
confidence: 99%
“…The aggregate cost of university education and the impact of student debt has previously been explored by other authors and in government reports (Australian Government, 2008;Burdman, 2005;Craig & Raisanen, 2014;DEEWR, 2012;Linsenmeier, Rosen, & Rouse, 2006;Norton & Cherastidtham, 2014;Tumen & Shulruf, 2008;Waddell & Singell, 2011). However, few authors have considered the attitudes of students towards university fees collected to provide the ancillary services and amenities that augment the experience and character of university life, but are not of an academic nature.…”
Section: Introductionmentioning
confidence: 99%
“…The second set of regressions examine the impact of the total amount of nonloan aid the student received, including merit‐based scholarships, athletic scholarships, grants, work‐study aid, and other nonloan aid. Several studies have found that greater amounts of nonloan aid are associated with higher rates of college attendance, retention, graduation, and career choice (Waddell and Singell Jr ; Dynarski ; DesJardins and McCall ; Castleman and Long ; Minicozzi ). Finally, we restrict the sample to students who borrow to finance their education and use the ratio of loans to tuition charges to examine the effects of the intensive margin.…”
Section: Methodsmentioning
confidence: 99%